2004
DOI: 10.1002/ajmg.b.30068
|View full text |Cite
|
Sign up to set email alerts
|

Candidate gene association studies of genes involved in neuronal cholinergic transmission in Alzheimer's disease suggests choline acetyltransferase as a candidate deserving further study

Abstract: Consistent deficits in the cholinergic system are evident in the brains of Alzheimer's Disease (AD) patients, including reductions in the activities of acetylcholine, acetylcholinesterase (AChE), and choline acetyltransferase (ChAT), increased butyrylcholinesterase (BChE) activity, and a selective loss of nicotinic acetylcholine receptors (nAChRs). Accordingly, we have analyzed polymorphisms in the genes encoding AChE, ChAT, BChE, and several of the subunit genes from neuronal nAChRs, for genetic associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 35 publications
1
45
1
Order By: Relevance
“…In addition, we also found suggestive associations of all 3 SNPs with cognitive function as measured by MMSE score. Originally, Mubumbila et al [12] reported a significant association of the exon 5 SNP in 122 LOAD cases and 112 controls in a French-German population, but it was not confirmed in subsequent studies [3,5,15]. Recently, Kim et al [8] reported a significant association of this SNP among APOE*4 carriers in a Korean sample.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also found suggestive associations of all 3 SNPs with cognitive function as measured by MMSE score. Originally, Mubumbila et al [12] reported a significant association of the exon 5 SNP in 122 LOAD cases and 112 controls in a French-German population, but it was not confirmed in subsequent studies [3,5,15]. Recently, Kim et al [8] reported a significant association of this SNP among APOE*4 carriers in a Korean sample.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of SNP rs2230806 (R219K variant) in exon 7 of the ABCA1 gene (c.969A→G) was determined for each sample. The presence of the missense mutation at nucleotide 969 (AGG to AAG), which leads to the replacement of arginine with lysine at codon 219, was evaluated in genomic DNA by polymerase chain reaction (PCR)-RFLP analysis, according to methods described by Cook et al (17). A 333-bp PCR product was generated using forward 5'-TCC AAAAGACTTCAAGGACCCAGCT-3' and reverse 5'-AAGT CATGCTGTCCAAGGAAAA-3' primers.…”
Section: Methodsmentioning
confidence: 99%
“…These findings have led to the cholinergic hypothesis of AD and the development by pharmaceutical companies of therapies targeting cholinergic molecular components, so far mainly targeting the hydrolytic breakdown of ACh by AChE (Arneric et al, 2007). Genetic association studies investigating single nucleotide polymorphisms point to roles for cholinergic signaling components such as the synthetic enzyme ChAT, the inactivating enzyme AChE, and ␣4␤2 nAChRs in AD (Cook et al, 2004(Cook et al, , 2005Vasto et al, 2006). The most vulnerable neurons in AD seem to be those expressing high levels of nAChRs, particularly those containing the ␣7 subunit (D'Andrea and Nagele, 2006), and the numbers of nAChRs as well as some of their associated proteins change in AD (Martin-Ruiz et al, 1999;Gotti et al, 2006;Sabbagh et al, 2006).…”
Section: Nicotinic Acetylcholine Receptors: Structure Function mentioning
confidence: 99%